A self-assembled gold-spiked nanosphere based paper assay for sensitive glucose detection - Dai, Xin-Yi; Shi, Xiao-Jie; Wu, Yu; Zhang, Ting-Ting; Song, Tian-Shun; Li, Xiang-Ling; Xie, Jing-Jing (Analytical methods, 2025)
Glucose detection plays a crucial role in health monitoring, and the development of efficient and convenient detection platforms is highly desired. This study presents a sensitive and convenient detection system for non-invasive glucose detection in sweat, which is formed by combining the self-assembled gold-spiked nanosphere (GSN) nanozyme with paper-based analytical devices (PADs). The GSN nanozyme exhibits excellent glucose oxidase-like catalytic activity, significantly enhancing the sensitivity and selectivity of glucose detection. By integrating the self-assembled GSN nanozyme with a paper-based assay, this system enables fast, cost-effective, and non-invasive glucose detection and shows minimal interference from common substances found in sweat, demonstrating its potential for practical biomedical applications. We constructed a gold-spiked nanosphere nanozyme-based paper platform for non-invasive detection of glucose.